2019
DOI: 10.2174/1874609811666180223154436
|View full text |Cite
|
Sign up to set email alerts
|

At the Crossroads Between Neurodegeneration and Cancer: A Review of Overlapping Biology and Its Implications

Abstract: We argue that a detailed understanding of the biologic and genetic relationships between cancer and neurodegeneration can guide future efforts in designing disease-modifying therapeutic interventions. Lastly, strategies that target aging may prevent or delay both conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 146 publications
1
78
0
Order By: Relevance
“…However, there are no available experimental data on the mechanism(s) leading to reduced LMTK2 level. Nonetheless, a recent theory suggesting that neurodegeneration is the cancer of neurons may serve as a potential explanation [39][40][41]. Because neurons are terminally differentiated cells it is possible that certain noxious stimuli which cause uncontrolled proliferation in other organs result in aberrant cell cycle re-entry with degenerative changes and apoptosis in nerve cells [42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no available experimental data on the mechanism(s) leading to reduced LMTK2 level. Nonetheless, a recent theory suggesting that neurodegeneration is the cancer of neurons may serve as a potential explanation [39][40][41]. Because neurons are terminally differentiated cells it is possible that certain noxious stimuli which cause uncontrolled proliferation in other organs result in aberrant cell cycle re-entry with degenerative changes and apoptosis in nerve cells [42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…We need to mention that PARK6 (PINK1) may also have a protective and anti-tumor function and that both genes, Park2 and Park6 (PINK 1), possess not only anti-inflammatory but also tumor-suppressive characteristics. On the other side, PARK7 (DJ-1) has been described as an oncogene, and this condition appears to be mediated by the inhibitor function on the PTEN, as mentioned beforehand, a known tumor suppressor gene (Houck et al, 2018).…”
Section: Parkinson's Diseasementioning
confidence: 94%
“…Gene mutations, transcriptional, protein, and mitochondrial dysregulation in opposite directions play a substantial role in these disorders. In this sense, a tumor-suppressor gene with a transcriptional role, p53, is downregulated in several tumors and upregulated in PD, AD, and HD (Houck et al, 2018). Therefore, a link between cancer and neurodegeneration is plausible as they share several genes and biological pathways, including inappropriate activation and deregulation of the cell cycle, resulting in opposite endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests a role of gene expression regulators in the shared genetic etiology between AD and cancer, and implies that some shared variants modulate disease risk. Increasing evidence suggest that there are common pathophysiological features in both diseases, such as DNA damage, oxidative stress, mitochondrial dysfunction, metabolic dysregulation, and inflammation (Driver, 2014;Houck et al, 2018). Moreover, single nucleotide polymorphism (SNP)-trait genome-wide association studies (GWAS) have shown positive genetic correlations between AD and cancer (Feng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%